"Short term surgical complications after subthalamic deep brain stimulation for Parkinson's disease: does old age matter?". Issue 1 (December 2015) - Levi, Vincenzo; Carrabba, Giorgio; Rampini, Paolo; Locatelli, Marco
Abstract Background Patients aged 65 years and older are not traditionally considered optimal candidates for subthalamic deep brain stimulation (STN-DBS), mainly for their presumed increased incidence of surgical complications. The aim of this study was to assess STN-DBS surgery safety in relation to age. Methods A total of 107 consecutive patients undergoing bilateral STN-DBS at our institution between 2002 and 2014 were retrospectively stratified according to age in two groups (Young group < 65 years old; Elderly group ≥ 65 years old;). Rate of short-term surgical complications (within 90 days) was reviewed and compared between the two groups. Results Pre-operative baseline data were comparable between the two groups. The 90-days post-operative mortality rate was 0%. Overall incidence of complications related to surgery was 6, 54%. In the Elderly group we observed 3 post-operative intra-cerebral haematomas (7, 89%), 1 requiring urgent surgical evacuation. In the Young group we observed 2 post-operative asymptomatic intra-cerebral haematomas (2, 89%) and 2 wound infections (2, 89%), 1 requiring system removal. No others surgical complications were noticed in both groups. Conclusions Chronological age ≥ 65 years old should not be considered alone as exclusion criteria to STN-DBS surgery.